Personnel real time dosimetry in interventional radiology. Issue 12 (December 2016) - Servoli, L.; Bissi, L.; Fabiani, S.; Magalotti, D.; Placidi, P.; Scorzoni, A.; Calandra, A.; Cicioni, R.; Chiocchini, S.; Dipilato, A.C.; Forini, N.; Paolucci, M.; et al.
Highlights: A wireless real-time dosimeter for interventional radiology has been developed. Tested on more than 40 procedures with linear response to dose. It records a trace of dose-rate at 5 Hz frequency to be used for self-training. Abstract: Interventional radiology and hemodynamic procedures have rapidly grown in number in the past decade, increasing the importance of personnel dosimetry not only for patients but also for medical staff. The optimization of the absorbed dose during operations is one of the goals that fostered the development of real-time dosimetric systems. Indeed, introducing proper procedure optimization, like correlating dose rate measurements with medical staff position inside the operating room, the absorbed dose could be reduced. Real-time dose measurements would greatly facilitate this task through real-time monitoring and automatic data recording. Besides real-time dose monitoring could allow automatic data recording. In this work, we will describe the calibration and validation of a wireless real-time prototype dosimeter based on a new sensor device (CMOS imager). The validation measurement campaign in clinical conditions has demonstrated the prototype capability of measuring dose-rates with a frequency in the range of few Hz, and an uncertainty smaller than 10%.